Causality in the Sciences 2011
DOI: 10.1093/acprof:oso/9780199574131.003.0018
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive causality test based on the singular spectrum analysis

Abstract: In this paper, we consider the concept of casual relationship between two time series based on the singular spectrum analysis. We introduce several criteria which characterize this causality. The criteria are based on the forecasting accuracy and the predictability of the direction of change. The performance of the proposed tests is examined using different real time series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The latter has been applied to test for nonlinear causality between energy and output (Chiou-Wei et al, 2008) but is not applicable to non-stationary data and has several other shortcomings (Hassani et al, 2010). Chiou-Wei et al (2008) difference their data in order to apply the test, but this throws away the information on the long-run relationship between the variables.…”
Section: Granger Causality Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been applied to test for nonlinear causality between energy and output (Chiou-Wei et al, 2008) but is not applicable to non-stationary data and has several other shortcomings (Hassani et al, 2010). Chiou-Wei et al (2008) difference their data in order to apply the test, but this throws away the information on the long-run relationship between the variables.…”
Section: Granger Causality Testingmentioning
confidence: 99%
“…Chiou-Wei et al (2008) difference their data in order to apply the test, but this throws away the information on the long-run relationship between the variables. Hassani et al (2010) present a method based on singular spectrum analysis that they claim can cope with non-stationary series. Another kernel-based approach is developed by Sun (2008).…”
Section: Granger Causality Testingmentioning
confidence: 99%
“…Generally, in the standard or basic SSA, almost all of the current studies suggested the window length should be larger but not greater than half of the time series length to achieve better separately of trend and residual. This means that if the length of the time series is , then the window length for the lagged vectors in time series embedding is about 2 ≤ ≤ /2 [13,25,26,31,36]. As the window length is an integer, thus there are many satisfied values of as the tuning parameter that can be used to cover the time series embedding.…”
Section: Related Workmentioning
confidence: 99%
“…Given a one-dimensional time series data = ( 1 , 2 , … , ) with 1 ≤ ≤ of length . Let = ( , +1 , … , + −1 ) is a sub-series vector of with 1 < < , 1 ≤ ≤ , and = − + 1 [25,31]. The window length is an integer between 1 and .…”
Section: Time Series Embeddingmentioning
confidence: 99%
See 1 more Smart Citation